Classificação climática e disponibilidade hídrica no auxílio do planejamento ambiental e socioeconômico no município de Goiás (GO) : a exemplo o projeto de Assentamento Mosquito - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The physicist aspect of the weather, water and relief are preponderant to the occupation of the territory. The climate influence on the man in many ways, and its anthropic action with the practice of its activities also have influence on the climate. Similarly, the hydraulics availability conditioned is to the weather, anthropogenic action can affect it. In face of the huge importance that the weather exert up on society and on the natural aspects (water, relief, fauna and flora), it was and it is necessary studies that propitiate bigger knowledge about it is dynamic. On this perspective, the following research was developed having as a studying goal the investigation of the climate in the Goiás County and on the “Mosquito Settlement” project, also the analyses of the water bodies contained in the settlement, with purpose of establishing an inter-relation between local weather and the hydric availability locality. And from the climate – water – man interrelationship, propose the applicability of implementation actions based at the Agroecosystem actions, considering the occupation and transformation that took place in this territory. On the survey, it considered is the categories landscape and territory, since; this zone constituted is from the Land Reform fight as an emerged turf. Territory that begins to be molded from the ones that there reside. The research contemplated is with the quali-quantitative approach, developed by the primary and secondary. To the reanalysis of data on the precipitation and temperature, it was given by the algorithm CHELSA (Climatology at high resolution for the earth’s land surface areas) and processed with help of software QGIS 3.16, with application of the methodology developed by Novais (2019). With the help of field work records and the result of the Climatological Water Balance, the relationship between climate – water – man was made, and water availability. This way, it was identify on Goiás County the existence of a dozen climate units, seven of them belonging to the semidry Climate Subdomain, and five to the semi humid Climate Subdomain, which proves that not uniformity of the weather in the area of study. In that regard, identify as example; four mesoclimate, one in the P. A. Mosquito area and the other on the urban perimeter of Goiás County, the third is on the northwest of the County and the last on Serra Dourada. Ascertain, with the assistance of the fieldwork pictures and the Climatological Water Balance, the reduce of hydric availability in the settlement area, resulted of the climate issue that evidenced a period of seven dry months with hydric deficit, and only five months with hydric surplus and the anthropogenic actions. This scenery lead to the suggestion of measures based on agroecosystem, mainly the one that aim the soil preservation, consequently the water.
Climate classification and hydrous availability in the environment assistance planning and socioeconomic in the county of Goiás : as the exemplo the project Mosquito settlement
Keywords: Clima; Unidades climáticas; Mesoclima; Corpos hídricos; Assentamento rural; Weather. Rural Settlement; Climate units; Mesoclimate; Hydric bodies; Rural settlement; GEOCIENCIAS::GEOGRAFIA FISICA; GEOGRAFIA FISICA::CLIMATOLOGIA GEOGRAFICA; GEOGRAFIA FISICA::HIDROGEOGRAFIA; GEOGRAFIA FISICA::GEOCARTOGRAFIA